A genealogy of computer-generated narrative. Issue 1 (1st March 2017) - Rose, Ellen
Responding to contemporary representations of computer-generated writing, which depict it as an inevitable and evolutionary development, this Foucauldian genealogy explores discourses on the digital production of narrative from the 1980s to the present, detailing the ways in which programmers, authors and scholars have negotiated different ways of thinking about what digital storymaking is and what ends it should serve. This article also inquires into the implications these competing views on computer-generated narrative have for readers, writers, computer users and society as a whole.